Exploring the molecular genetic foundations of cancer biology and how biomedical advances are made in an advanced undergraduate course. Issue 4 (15th April 2019) - Alexander, Stephen; Hannink, Mark
Abstract: We describe an advanced, inquiry driven undergraduate course in Cancer Biology that combines faculty lectures typical of undergraduate courses with literature‐driven discussions typical of graduate courses. As a capstone course, one goal of this course is to integrate knowledge from previous coursework in physiology, cell and molecular biology, genetics, and chemistry, so that students acquire a state‐of‐the‐art understanding of cancer and cancer treatment. A related goal is for students to learn, from the primary literature, how science is performed and how new scientific knowledge is used to improve cancer treatment. We report on the development of this course and the methods used to accomplish the course goals. We present the results of a 5‐year survey that provides a detailed picture of the demographics of the class and demonstrates that the course results in improved understanding of both cancer biology and how science is performed. Student responses to our survey strongly support the use of original literature as a teaching tool. We suggest that incorporation of primary literature into advanced undergraduate science courses is an effective approach for improving scientific literacy. © 2019 International Union of Biochemistry and Molecular Biology, 47(4):408–416, 2019.